2000
DOI: 10.1042/bj3450595
|View full text |Cite
|
Sign up to set email alerts
|

Neuroserpin is expressed in the pituitary and adrenal glands and induces the extension of neurite-like processes in AtT-20 cells

Abstract: Two cDNAs encoding the serine protease inhibitor (serpin) neuroserpin were cloned from a rat pituitary cDNA library (rNS-1, 2922 bp; rNS-2, 1599 bp). In situ hybridization histochemistry showed neuroserpin transcripts in the intermediate, anterior and posterior lobes of the pituitary gland and medullary cells in the adrenal gland. Expression of rNS-1 mRNA was restricted to selected cells in the pituitary gland. Analysis of purified secretory-granule fractions from pituitary and adrenal tissues indicated that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Third, Spn4.1 has a C-terminal extension unique among the annotated Drosophila serpins but closely resembling the C-terminal region of neuroserpin (Osterwalder et al, 1996;Krueger et al, 1997;Schrimpf et al, 1997;Hill et al, 2000). Although the function of the C terminus of neuroserpin is not known, the Spn4.1 C terminus perfectly matches the K/H-D-E-L consensus for the ER retention signal for soluble proteins (Pelham, 1990), suggesting that this isoform functions in the secretory pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Third, Spn4.1 has a C-terminal extension unique among the annotated Drosophila serpins but closely resembling the C-terminal region of neuroserpin (Osterwalder et al, 1996;Krueger et al, 1997;Schrimpf et al, 1997;Hill et al, 2000). Although the function of the C terminus of neuroserpin is not known, the Spn4.1 C terminus perfectly matches the K/H-D-E-L consensus for the ER retention signal for soluble proteins (Pelham, 1990), suggesting that this isoform functions in the secretory pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Neuroserpin is an axonally secreted member of the serine proteinase inhibitor or serpin superfamily (11)(12)(13)(14)(15). Members of this family share a similar molecular architecture based on a dominant ␤-sheet A and a mobile inhibitory reactive center loop (16).…”
mentioning
confidence: 99%
“…32 The effect of pH on the stability of neuroserpin is particularly important as this protein is stored in the acidic environment of the dense-core vesicles before secretion from the neurone. 20,[34][35][36] We report here that neuroserpin is resistant to polymer formation at acidic pH. This effect is not mediated by the shutter domain histidine but by other histidines, in particular His119 and His138.…”
Section: Introductionmentioning
confidence: 72%
“…37 The stabilization of neuroserpin at low pH may be physiologically relevant as neuroserpin is stored in the dense-core vesicles of cells that have a pH between 5.0 and 6.0, before its release in the extracellular environment. 20,[34][35][36] At neutral pH, the instability of neuroserpin might contribute to its faster clearance, either by forming unstable complexes with tPA 7,45 or by internalization by the LDL receptor-related protein. 46 In conclusion, this study showed the importance of the interaction between strand 1A and helix E in the polymerization of neuroserpin.…”
Section: Other Histidines Are Involved In Neuroserpin Polymerizationmentioning
confidence: 99%